Sorghum Allelochemistry and Its Use as a Bioherbicide: A Comprehensive Review - Edi Susilo; Parwito Parwito; Dia Novita Sari; Susi Handayani; Andreani Kinata; Hesti Pujiwati; Dian Novita; Tatik Raisawati (PUCUK : Jurnal Ilmu Tanaman, 2025)
Sorghum bicolor is a potential plant source for bioherbicide phytochemicals via allelopathy. Allelochemicals from sorghum plants and phenolic compounds have repelled and inhibited the growth and germination of weed seeds during several rounds of pulling and burning. This study compiled the latest literature to understand phenolic allelochemicals regarding the potential for sustainable weed management. This review shows that sorghum bioherbicidal phytochemicals have the potential to inhibit weed germination and growth by physiologically and biochemically altering weed physiology and biochemistry, including inhibition of photosynthesis via membrane destruction. Disruption of growth-regulating hormones, the formation of oxidative stress characterized by increased lipid peroxidation, and the induction of cell membranes. This is determined by external environmental factors, soil microbial dynamics, the cultivar genotype, and variations in the methods used to extract and apply them. In addition to root exudates and residues, sorghum intercropping has been shown to promote soil health and enhance weed suppression. Sorghum intercropping in sustainable systems offers an environmentally friendly alternative to synthetic herbicides. This offers a path for future field research on bioherbicide formulations to investigate safe concentration thresholds and the phytochemicals that are only partially stable in the field. Overall, sorghum has broad potential for intercropping systems, sustainable agriculture, and efficient, adaptive weed management.